Doing Quality Research: A Journey for Educators การทำวิจัยให้มีคุณภาพ: การเดินทางสำหรับนักการศึกษา - Pandian, Ambigapathy (วารสารรามคำแหง ฉบับมนุษยศาสตร์, 2014)
Abstract The growing significance of multimodal information and communication systems have pushed the need for a more adequate research agenda on new teaching and learning practices as teachers, students and educationists engage in new forms of establishing knowledge, education and scholarship culture. This paper traces some of the dramatic developments taking place in the field of teaching and learning in Malaysia with a focus on the researcher's experiences encountered in working with different groups in education. Some of the issues discussed include doing quality research by asking relevant questions and working on issues that create social impact as well as appreciating research ethics. By way of conclusion, this paper calls for more collaborative research practices that involve several interest groups that will bring not only fruitful research and changes but also develop shared linkages, materials and human resources that contribute towards knowledge producing communities. บทคัดย่อ การเปลี่ยนแปลงของระบบการสื่อสารและการเพิ่มขึ้นอย่างรวดเร็วของสารสนเทศ ทำให้การวิจัยทางการศึกษาต้องปรับเปลี่ยนตามไปด้วย โดยเฉพาะในประเด็นเกี่ยวกับการเรียนและการสอน อาจารย์ นักศึกษา และนักการศึกษาได้ให้ความสนใจในการพัฒนาความรู้ การศึกษา และวัฒนธรรมมากขึ้น บทความนี้ได้กล่าวถึงการพัฒนาการเรียนการสอนของประเทศมาเลเซียหลายประเด็น โดยผู้วิจัยได้นำเสนอประสบการณ์การทำงานด้านการศึกษากับผู้คนหลายกลุ่ม และกล่าวถึงแนวทางการทำวิจัยให้มีคุณภาพ โดยเฉพาะการสร้างสรรค์งานที่ส่งผลกระทบ ต่อสังคมและการคำนึงถึงจรรยาบรรณการวิจัย นอกจากนี้ ผู้วิจัยยังได้กล่าวถึงประโยชน์ของ การร่วมมือและการรวมกลุ่มกันทำวิจัย เพื่อให้ได้งานวิจัยที่มีความหลากหลายและเกิด การเชื่อมโยงและบูรณาการศาสตร์ต่าง ๆ เข้าด้วยกัน รวมทั้งทำให้มีการใช้ทรัพยากรร่วมกันอย่างมีประสิทธิภาพ โดยเฉพาะทรัพยากรบุคคล วัตถุดิบ และอื่น ๆ ซึ่งจะเป็นพื้นฐานของสังคมวิชาการต่อไป